2018
DOI: 10.1038/s41598-018-34148-6
|View full text |Cite
|
Sign up to set email alerts
|

Loss of progesterone receptor membrane component 1 promotes hepatic steatosis via the induced de novo lipogenesis

Abstract: Non-alcoholic fatty liver disease (NAFLD) results from triglyceride accumulation within the liver and some of them advances to non-alcoholic steatohepatitis (NASH). It is important to note that in NAFLD development, hepatic de novo lipogenesis (DNL) derives from excess carbohydrates and fats under a condition of excess energy through β-oxidation. As a main regulator for DNL, sterol regulatory element-binding protein 1 (Srebp-1) forms complex with progesterone receptor membrane component 1 (Pgrmc1). To investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 51 publications
0
48
0
Order By: Relevance
“…Progesterone receptor membrane component 1 (PGRMC1) is a novel cell surface receptor that is involved in cytochrome activities, drug metabolism, cholesterol synthesis, and steroid synthesis 10 , 11 . Recently, we found that PGRMC1 is involved in fatty liver amelioration 12 . However, it was also reported that PGRMC1 is a functional part of the GLP-1 receptor (GLP-1R) promoting insulin secretion in beta cells (β cells) 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Progesterone receptor membrane component 1 (PGRMC1) is a novel cell surface receptor that is involved in cytochrome activities, drug metabolism, cholesterol synthesis, and steroid synthesis 10 , 11 . Recently, we found that PGRMC1 is involved in fatty liver amelioration 12 . However, it was also reported that PGRMC1 is a functional part of the GLP-1 receptor (GLP-1R) promoting insulin secretion in beta cells (β cells) 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…PGRMC1 is a member of a multi‐protein progesterone‐binding complex and its biochemical function involves binding to heme and activating P450 proteins responsible for the metabolism of drugs, hormones, and lipids . SREBP1 forms a complex with PGRMC1 and promotes lipogenesis, one of the pathways exploited by cancer cells to acquire fatty acids for increased cell metabolism . PGRMC1 has been associated with advanced‐stage disease and poor prognosis in a number of cancers, including breast, lung, and ovarian cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Loss of PGRMC1 affects the SREBP-1/fatty acid homeostasis system [77], and PGRMC1 influences cell surface localization of insulin receptor and glucose transporters [26]. Chemical proteomics showed that PGRMC2 but not PGRMC1 promotes adipogenesis in 3T3-L1 preadipocytes following a gain of function interaction with a novel small molecule which displaced heme [78].…”
Section: Discussionmentioning
confidence: 99%